The pressure dependence of laminar flame speed of 2-methyl-2-butene/air flames in the 0.1–1.0 MPa range. Issue 11 (2nd November 2018) - Zhong, Bei-Jing; Zeng, Zhao-Mei; Peng, Hui-Sheng
ABSTRACT: Laminar flame speeds of 2-methyl-2-butene/air mixtures were measured in a constant volume combustion bomb at T 0  = 450 K, p  = 0.1–1.0 MPa, and φ  = 0.5–1.6. The dependence of laminar flame speed on pressure is described by an empirical formula, where the power exponent β is summarized as a function of equivalence ratios ( φ ). The maximum β at stoichiometric ratio indicates that the effect of pressure on flame is greater around the stoichiometric ratio and weaker at deviations from the stoichiometric ratio. Furthermore, analysis by chemical kinetic mechanism shows that elevated pressure is more sensitive to the reactions associated with the H and OH radicals and affects their concentration variation, and ultimately the laminar flame speed of 2-methyl-2-butene/air mixtures.